Aquatic Empididae (Diptera: Hemerodromiinae and Clinocerinae) of the Sierra Nevada, Spain, with the description of five new species - Ivković, Marija; Zamora-Muñoz, Carmen; Sainz-Bariaín, Marta; Sinclair, Bradley J. (Zootaxa, 2014)
In total 24 species of aquatic Empididae (Clinocerinae and Hemerodromiinae) are known from the Sierra Nevada Mountains of Spain, including five new species (Hemerodromia planti Ivković & Sinclair sp. nov., Kowarzia nevadensis Sinclair & Ivković sp. nov., Wiedemannia darioi Sinclair & Ivković sp. nov., W. horvati Ivković & Sinclair sp. nov. and W. vedranae Ivković & Sinclair sp. nov.). The new species are described, illustrated and distribution of all species listed. Wiedemannia (Philolutra) angelieri Vaillant and W. (Roederella) ouedorum Vaillant are newly recorded in Sierra Nevada and nine species are endemic to this region. A key to all 24 species of aquatic empidids is presented.